Practical Applications of the Concrete Operational Stage in Jean Piaget’s Theory of Cognitive Development - Wang, Baoxing (Journal of Educational Research and Policies, 2025)
This study focuses on the “concrete operational” stage within the framework of Piaget’s theory of cognitive development. It systematically reviews the core concepts of the cognitive development theory and combines this with in-depth analysis of empirical cases. The research unfolds from three perspectives: theoretical explanation, practical application, and critical reflection, aiming to reveal the theory’s explanatory power regarding the patterns of children’s cognitive development, while also exploring implementation strategies in game design, reading arrangements, and teaching adjustments. Furthermore, it provides a dialectical analysis of the theory’s limitations, offering theoretical foundations and practical references for research on children’s cognitive development and educational practices.